The Role of the Ventromedial Prefrontal Cortex in Public Good and Public Bad Games: Evidence From a tDCS Study - Chen, Yuyou; Lu, Xinbo; Li, Yuzhen; Zeng, Lulu; Yu, Ping; Luo, Jun; Ye, Hang; Zheng, Wanjun (Frontiers in Behavioral Neuroscience, 2021)
Although humans constitute an exceptionally cooperative species that is able to collaborate on large scales for common benefits, cooperation remains a longstanding puzzle in biological and social science. Moreover, cooperation is not always related to resource allocation and gains but is often related to losses. Revealing the neurological mechanisms and brain regions related to cooperation are important for reinforcing cooperation-related gains and losses. Recent neuroscience studies have found that the decision-making process of cooperation is involved in the function of the ventromedial prefrontal cortex (VMPFC). In the present study, we aimed to investigate the causal role of the VMPFC in cooperative behavior concerning gains and losses through the application of transcranial direct current stimulation (tDCS). We integrated cooperation-related gains and losses into a unified paradigm. Based on the paradigm, we researched cooperation behaviors regarding gains in standard public good games and introduced public bad games to investigate cooperative behavior regarding losses. Our study revealed that the VMPFC plays different roles concerning gains and losses in situations requiring cooperation. Anodal stimulation over the VMPFC decreased cooperative behavior in public bad games, whereas stimulation over the VMPFC did not change cooperative behavior in public good games. Moreover, participants’ beliefs about others’ cooperation were changed in public bad games but not in public good games. Finally, participants’ cooperative attitudes were not influenced in public good or in public bad games under the three stimulation conditions.